EXPERIMENTAL STUDY OF SOME PROPERTIES OF THE SPARKING DISCHARGE IN ATMOSPHERIC AIR - Talal, Shamil K. (Science Journal of University of Zakho, 2024)
The current experimental study investigates some aspects of the electrical discharge properties between two planar electrodes. These properties involve the relationships of the minimum sparking potential to the electrode separation, the spark repetition rate, and the distribution of discharge pulse height concerning both the applied voltage and electrode separation. These discharge parameters tend to show nonlinear relationship with both applied voltage and electrode separation.